A water-resistant and rust-proof quick-drying epoxy alkyd varnish and its preparation process
By using epoxy alkyd resin and specific additives in alkyd varnish, combined with the synergistic effect of sheet-like graphene and complement-modulation coordinating agents, the problems of poor quick drying performance and low impact resistance of existing alkyd varnish are solved. , achieving significant improvements in the product's fast drying, impact resistance, salt spray and rust resistance and water resistance stability.
Patent Information
- Application Number
- CN202410711483.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-06-04
AI Technical Summary
The existing alkyd varnish has poor fast drying performance, low impact resistance, and insufficient salt spray rust resistance and water resistance, which limits the efficiency of the product.
Using epoxy alkyd resin as the matrix material, soybean oil, silane coupling agent, curing agent and drying agent, and combined with emphasis modifier and complement coordinator based on flake graphene, optimized through a specific preparation process Product performance.
It significantly improves the fast drying and impact resistance of the product, and improves the salt spray resistance and water resistance, and improves the efficiency of the product.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy alkyd varnish, and in particular to a water-resistant and rust-proof quick-drying epoxy alkyd varnish and a preparation process thereof. Background Art
[0002] Alkyd resin is cheap, easy to construct, has abundant raw material sources, low acid value, and can be dissolved in a variety of organic solvents. It is suitable for surface coating of all wood, plastic, and metal, and can be mixed with a variety of synthetic resins. However, alkyd resin has the following performance problems: slow drying of the coating, low hardness, poor water resistance, and poor corrosion resistance.
[0003] Existing alkyd varnishes have poor quick-drying performance and low impact resistance. It is difficult for the product to achieve coordinated improvement in quick drying and impact resistance. The product's salt spray resistance, rust resistance and water resistance stability are poor, which further limits the product's use efficiency. Summary of the invention
[0004] In view of the defects of the prior art, the object of the present invention is to provide a water-resistant and rust-proof quick-drying epoxy alkyd varnish and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a water-resistant and rust-proof quick-drying epoxy alkyd varnish, comprising the following raw materials in parts by weight:
[0007] 35-45 parts of epoxy alkyd resin, 8-12 parts of flaky graphene-based stress modifier, 4-8 parts of soybean oil, 5-7 parts of compensating and adjusting agent, 4-6 parts of silane coupling agent, 4-6 parts of curing agent, 0.2-0.3 parts of drying agent, and 30-35 parts of solvent.
[0008] Preferably, the preparation method of the epoxy alkyd resin is as follows: a polyol of neopentyl glycol and a polyacid of adipic acid are mixed in a weight ratio of 1:2, xylene accounting for 15% of the total amount of neopentyl glycol is added, the mixture is heated to 120°C for reaction for 1 to 2 hours, and then the mixture is heated to 160°C for reaction until complete to obtain an alkyd resin; bisphenol A epoxy resin, alkyd resin and triethanolamine are mixed in a weight ratio of 10:40:1.5, heated to 105°C for reaction for 2 to 4 hours, and the material is filtered to obtain an epoxy-modified alkyd resin;
[0009] The drying agent is butyl tin oxide; the solvent is ethyl acetate solvent; the curing agent is ethylenediamine; and the silane coupling agent is silane coupling agent KH560.
[0010] Preferably, the preparation method of the graphene-based stress modifier is:
[0011] S01: The flake graphene is first mixed with a sufficient amount of a 2% hydrochloric acid solution, then washed with water and dried, the dried flake graphene is heat treated at 210-230°C for 5-10 minutes, and then the reaction temperature is cooled to 60°C at a rate of 2-5°C / min, kept warm, and set aside;
[0012] S02: Preparation of stress solution:
[0013] S021: Add 2-4 parts of carboxymethyl cellulose to 5-8 parts of sodium lignin sulfonate solution, and then add 1-2 parts of stearic acid and 0.25-0.35 parts of silane coupling agent KH550 to obtain a conditioning solution;
[0014] S022: Add nano-silicon dioxide into the phosphate buffer solution in a weight ratio of 2:(5-7) and mix thoroughly to obtain a nano-silicon dioxide dispersion;
[0015] S023: The nano-silicon dioxide dispersion and the toning liquid are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h to obtain a stress liquid;
[0016] S03: The flake graphene kept warm in S01 and the stressing liquid are stirred in a weight ratio of 3:7. After the stirring is completed, the mixture is filtered and dried to obtain a stressing modifier based on flake graphene.
[0017] Preferably, the pH value of the phosphate buffer solution is 5.0-5.5; and the mass fraction of the sodium lignin sulfonate solution is 4-6%.
[0018] Preferably, the stirring treatment is first carried out at a stirring speed of 750 to 850 r / min for 10 to 15 min, and then the speed is reduced to 300 to 350 r / min, and stirring is continued for 35 to 40 min.
[0019] Preferably, the preparation method of the tonic and synergistic agent is:
[0020] S11: treating the silicon carbide whiskers with proton irradiation at a power of 400 to 450 W for 10 to 15 minutes, and obtaining irradiated whiskers after the irradiation is completed;
[0021] S12: immersing the irradiated whiskers into a sufficient amount of lanthanum solution until fully immersed, filtering and drying after the immersion is completed, to obtain a lanthanum-modified whisker agent;
[0022] S13: mixing the lanthanum-modified whisker agent and the hydroxyapatite-doped restorative modifying liquid in a weight ratio of 5:2 and subjecting them to ball milling treatment. After the ball milling is completed, washing and drying are performed to obtain a restorative modifying agent. The mixing ball milling speed is 1000-1500 r / min, and the ball milling is performed for 1 hour.
[0023] Preferably, the lanthanum solution is a lanthanum nitrate solution with a mass fraction of 2 to 5%; the ultrasonic power for full immersion is 350 to 380 W, and the immersion time is 15 to 25 min.
[0024] Preferably, the preparation method of the hydroxyapatite-doped tonic modifying liquid is:
[0025] The hydroxyapatite, chitosan solution and nano-silica sol are first mixed thoroughly in a weight ratio of (3-5): (7-9): 1 to obtain a compounding solution;
[0026] Yttrium oxide and sodium dodecylbenzene sulfonate solution are mixed in a weight ratio of 2:5 to obtain yttrium oxide agent; then, 5-10% of the total amount of the re-adjusting liquid and 2-5% of the total amount of sodium alginate are added to the re-adjusting liquid, and the mixture is further fully mixed to obtain a hydroxyapatite-doped remedial modified liquid.
[0027] Preferably, the mass fraction of the chitosan solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 5-8%.
[0028] The invention also provides a preparation process of a water-resistant and rust-proof quick-drying epoxy alkyd varnish, which comprises the following steps: the raw materials are mixed uniformly according to a proportion to obtain the quick-drying epoxy alkyd varnish of the invention.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The quick-drying epoxy alkyd varnish of the present invention adopts epoxy alkyd resin as a base material, and soybean oil, silane coupling agent, curing agent and drier are added as functional additives, and the added emphasizing modifier and supplementary adjusting agent based on flake graphene are coordinated and matched, and the quick-drying and impact resistance of the product are coordinated and improved, and the salt spray and rust resistance and water resistance stability of the product are significantly improved;
[0031] The epoxy alkyd resin is prepared by preparing an alkyd resin by combining polyols, polyacids and xylene, and then the epoxy modified alkyd resin is obtained by modifying the epoxy resin and triethanolamine to optimize the performance stability of the product matrix. At the same time, the flaky graphene-based stress modifier uses flaky graphene to be treated with hydrochloric acid, and then heat-treated at 210-230°C for 5-10 minutes, and then the reaction temperature is cooled to 60°C at a rate of 2-5°C / min. The active efficiency of the product is optimized by hydrochloric acid treatment and heat modification. At the same time, the stress liquid is ball-milled with the nano-silicon dioxide dispersion liquid and the grading liquid of the present invention. Improve and enhance the coordination and synergistic effect of flake graphene. The nano-silicon dioxide dispersion is dispersed in a phosphate buffer solution with nano-silicon dioxide, and then mixed with carboxymethyl cellulose, sodium lignin sulfonate solution, stearic acid and silane coupling agent KH550 to obtain a tackifying liquid. The raw materials in the tackifying liquid are coordinated with each other, and then the nano-silicon dioxide dispersion is synergistically improved. The nano-silicon dioxide in the flaky graphene is interspersed in the system to enhance the raw material interface of the system, and enhance the surface contact area of the system product, thereby improving the quick-drying performance and impact resistance of the product and optimizing the salt spray resistance and water resistance stability of the product.
[0032] The synergistic agent uses silicon carbide whiskers to be treated with proton irradiation to optimize the active efficiency of the whiskers, and then fully immersed in a lanthanum solution to obtain a lanthanum-modified whisker agent. The lanthanum-modified whisker agent is better coordinated with the hydroxyapatite-doped synergistic modifying liquid, further enhancing the coordination and synergy between the synergistic agent and the flaky graphene-based emphasizing modifier. The impact resistance and quick-drying coordination of the product are further enhanced, and the salt spray resistance, rust resistance and water resistance stability are significantly improved; the hydroxyapatite-doped synergistic modifying liquid is hydroxyapatite and chitosan. The solution and nano-silica sol are first treated with multiplexing to enhance the permeability and compatibility of hydroxyapatite in the multiplexing solution. At the same time, yttrium oxide and sodium dodecylbenzene sulfonate solution are matched to form yttrium oxide agent, so that the yttrium oxide agent is better coordinated with the multiplexing solution, and the addition of sodium alginate further enhances the mutual matching and mutual assistance between the raw materials. The point-like hydroxyapatite is coordinated with the whisker-like whisker structure to enhance the distribution effect of the synergistic agent in the system product, thereby further reinforcing the synergistic effect of the emphasized modifier based on flake graphene, and the performance of the product is further enhanced. DETAILED DESCRIPTION
[0033] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The water-resistant and rust-proof quick-drying epoxy alkyd varnish of the present embodiment comprises the following raw materials in parts by weight:
[0035] 35-45 parts of epoxy alkyd resin, 8-12 parts of flaky graphene-based stress modifier, 4-8 parts of soybean oil, 5-7 parts of compensating and adjusting agent, 4-6 parts of silane coupling agent, 4-6 parts of curing agent, 0.2-0.3 parts of drying agent, and 30-35 parts of solvent.
[0036] The preparation method of the epoxy alkyd resin of the present embodiment is as follows: a polyol of neopentyl glycol and a polyacid of adipic acid are mixed in a weight ratio of 1:2, xylene accounting for 15% of the total amount of neopentyl glycol is added, the mixture is heated to 120° C. for reaction for 1 to 2 hours, and then the mixture is heated to 160° C. for reaction until complete to obtain an alkyd resin; a bisphenol A type epoxy resin, an alkyd resin and triethanolamine are mixed in a weight ratio of 10:40:1.5, the mixture is heated to 105° C. for reaction for 2 to 4 hours, and the material is filtered to obtain an epoxy-modified alkyd resin;
[0037] The drying agent is butyl tin oxide; the solvent is ethyl acetate solvent; the curing agent is ethylenediamine; and the silane coupling agent is silane coupling agent KH560.
[0038] The preparation method of the graphene-based stress modifier of this embodiment is as follows:
[0039] S01: The flake graphene is first mixed with a sufficient amount of a 2% hydrochloric acid solution, then washed with water and dried, the dried flake graphene is heat treated at 210-230°C for 5-10 minutes, and then the reaction temperature is cooled to 60°C at a rate of 2-5°C / min, kept warm, and set aside;
[0040] S02: Preparation of stress solution:
[0041] S021: Add 2-4 parts of carboxymethyl cellulose to 5-8 parts of sodium lignin sulfonate solution, and then add 1-2 parts of stearic acid and 0.25-0.35 parts of silane coupling agent KH550 to obtain a conditioning solution;
[0042] S022: Add nano-silicon dioxide into the phosphate buffer solution in a weight ratio of 2:(5-7) and mix thoroughly to obtain a nano-silicon dioxide dispersion;
[0043] S023: The nano-silicon dioxide dispersion and the toning liquid are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h to obtain a stress liquid;
[0044] S03: The flake graphene kept warm in S01 and the stressing liquid are stirred in a weight ratio of 3:7. After the stirring is completed, the mixture is filtered and dried to obtain a stressing modifier based on flake graphene.
[0045] The pH value of the phosphate buffer solution in this embodiment is 5.0-5.5; the mass fraction of the sodium lignin sulfonate solution is 4-6%.
[0046] In the stirring process of this embodiment, the stirring speed is first 750 to 850 r / min for 10 to 15 minutes, and then the speed is reduced to 300 to 350 r / min, and the stirring is continued for 35 to 40 minutes.
[0047] The preparation method of the tonic and synergistic agent of this embodiment is:
[0048] S11: treating the silicon carbide whiskers with proton irradiation at a power of 400 to 450 W for 10 to 15 minutes, and obtaining irradiated whiskers after the irradiation is completed;
[0049] S12: immersing the irradiated whiskers into a sufficient amount of lanthanum solution until fully immersed, filtering and drying after the immersion is completed, to obtain a lanthanum-modified whisker agent;
[0050] S13: mixing the lanthanum-modified whisker agent and the hydroxyapatite-doped restorative modifying liquid in a weight ratio of 5:2 and subjecting them to ball milling treatment. After the ball milling is completed, washing and drying are performed to obtain a restorative modifying agent. The mixing ball milling speed is 1000-1500 r / min, and the ball milling is performed for 1 hour.
[0051] The lanthanum solution of this embodiment is a lanthanum nitrate solution with a mass fraction of 2 to 5%; the ultrasonic power for full immersion is 350 to 380 W, and the immersion time is 15 to 25 minutes.
[0052] The preparation method of the hydroxyapatite-doped remedial modified liquid of this embodiment is as follows:
[0053] The hydroxyapatite, chitosan solution and nano-silica sol are first mixed thoroughly in a weight ratio of (3-5): (7-9): 1 to obtain a compounding solution;
[0054] Yttrium oxide and sodium dodecylbenzene sulfonate solution are mixed in a weight ratio of 2:5 to obtain yttrium oxide agent; then, 5-10% of the total amount of the re-adjusting liquid and 2-5% of the total amount of sodium alginate are added to the re-adjusting liquid, and the mixture is further fully mixed to obtain a hydroxyapatite-doped remedial modified liquid.
[0055] The mass fraction of the chitosan solution in this embodiment is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 5-8%.
[0056] The method for preparing a water-resistant and rust-proof quick-drying epoxy alkyd varnish of the present embodiment comprises the following steps: the raw materials are mixed uniformly according to a proportion to obtain the quick-drying epoxy alkyd varnish of the present invention.
[0057] Embodiment 1:
[0058] The water-resistant and rust-proof quick-drying epoxy alkyd varnish of the present embodiment comprises the following raw materials in parts by weight:
[0059] 35 parts of epoxy alkyd resin, 8 parts of flaky graphene-based stress modifier, 4 parts of soybean oil, 5 parts of compensating agent, 4 parts of silane coupling agent, 4 parts of curing agent, 0.2 parts of drying agent, and 30 parts of solvent.
[0060] The preparation method of the epoxy alkyd resin of the present embodiment is as follows: a polyol of neopentyl glycol and a polyacid of adipic acid are mixed in a weight ratio of 1:2, xylene accounting for 15% of the total amount of neopentyl glycol is added, the mixture is heated to 120° C. for reaction for 1 hour, and then the mixture is heated to 160° C. for reaction until complete to obtain an alkyd resin; a bisphenol A type epoxy resin, an alkyd resin and triethanolamine are mixed in a weight ratio of 10:40:1.5, the mixture is heated to 105° C. for reaction for 2 hours, and the material is filtered to obtain an epoxy-modified alkyd resin;
[0061] The drying agent is butyl tin oxide; the solvent is ethyl acetate solvent; the curing agent is ethylenediamine; and the silane coupling agent is silane coupling agent KH560.
[0062] The preparation method of the graphene-based stress modifier of this embodiment is as follows:
[0063] S01: The flake graphene is first mixed with a sufficient amount of a 2% by mass hydrochloric acid solution, then washed with water and dried, the dried flake graphene is heat treated at 210°C for 5 minutes, and then the reaction temperature is cooled to 60°C at a rate of 2°C / min, kept warm, and set aside;
[0064] S02: Preparation of stress solution:
[0065] S021: Add 2 parts of carboxymethyl cellulose to 5 parts of sodium lignin sulfonate solution, and then add 1 part of stearic acid and 0.25 parts of silane coupling agent KH550 to obtain a conditioning solution;
[0066] S022: adding nano-silicon dioxide into the phosphate buffer solution at a weight ratio of 2:5 and mixing thoroughly to obtain a nano-silicon dioxide dispersion;
[0067] S023: The nano-silicon dioxide dispersion and the toning liquid are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h to obtain a stress liquid;
[0068] S03: The flake graphene kept warm in S01 and the stressing liquid are stirred in a weight ratio of 3:7. After the stirring is completed, the mixture is filtered and dried to obtain a stressing modifier based on flake graphene.
[0069] The pH value of the phosphate buffer solution in this example is 5.0; the mass fraction of the sodium lignin sulfonate solution is 4%.
[0070] In the present embodiment, the stirring process is first carried out at a stirring speed of 750 r / min for 1 min, and then the speed is reduced to 300 r / min and the stirring is continued for 35 min.
[0071] The preparation method of the tonic and synergistic agent of this embodiment is:
[0072] S11: treating the silicon carbide whiskers with proton irradiation at a power of 400 W for 10 minutes, and obtaining irradiated whiskers after the irradiation is completed;
[0073] S12: immersing the irradiated whiskers into a sufficient amount of lanthanum solution until fully immersed, filtering and drying after the immersion is completed, to obtain a lanthanum-modified whisker agent;
[0074] S13: The lanthanum-modified whisker agent and the hydroxyapatite-doped restorative modifying liquid are mixed and ball-milled in a weight ratio of 5:2. After the ball-milling is completed, the mixture is washed with water and dried to obtain a restorative modifying agent. The mixing ball-milling speed is 1000 r / min and the ball-milling is performed for 1 hour.
[0075] The lanthanum solution of this embodiment is a lanthanum nitrate solution with a mass fraction of 2%; the ultrasonic power for full immersion is 350W, and the immersion time is 15min.
[0076] The preparation method of the hydroxyapatite-doped remedial modified liquid of this embodiment is as follows:
[0077] The hydroxyapatite, chitosan solution and nano-silica sol are first mixed thoroughly in a weight ratio of 3:7:1 to obtain a compounding solution;
[0078] Yttrium oxide and sodium dodecylbenzene sulfonate solution are mixed in a weight ratio of 2:5 to obtain yttrium oxide agent; then, 5% of yttrium oxide agent and 2% of sodium alginate are added to the reconstituted liquid, and the mixture is further fully mixed to obtain a hydroxyapatite-doped remedial modified liquid.
[0079] The mass fraction of the chitosan solution in this embodiment is 2%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 5%.
[0080] The method for preparing a water-resistant and rust-proof quick-drying epoxy alkyd varnish of the present embodiment comprises the following steps: the raw materials are mixed uniformly according to a proportion to obtain the quick-drying epoxy alkyd varnish of the present invention.
[0081] Embodiment 2:
[0082] The water-resistant and rust-proof quick-drying epoxy alkyd varnish of the present embodiment comprises the following raw materials in parts by weight:
[0083] 45 parts of epoxy alkyd resin, 12 parts of flaky graphene-based stress modifier, 8 parts of soybean oil, 7 parts of compensating agent, 6 parts of silane coupling agent, 6 parts of curing agent, 0.3 parts of drying agent, and 35 parts of solvent.
[0084] The preparation method of the epoxy alkyd resin of the present embodiment is as follows: a polyol of neopentyl glycol and a polyacid of adipic acid are mixed in a weight ratio of 1:2, xylene accounting for 15% of the total amount of neopentyl glycol is added, the mixture is heated to 120° C. for reaction for 2 hours, and then the mixture is heated to 160° C. for reaction until complete to obtain an alkyd resin; a bisphenol A type epoxy resin, an alkyd resin and triethanolamine are mixed in a weight ratio of 10:40:1.5, the mixture is heated to 105° C. for reaction for 4 hours, and the material is filtered to obtain an epoxy-modified alkyd resin;
[0085] The drying agent is butyl tin oxide; the solvent is ethyl acetate solvent; the curing agent is ethylenediamine; and the silane coupling agent is silane coupling agent KH560.
[0086] The preparation method of the graphene-based stress modifier of this embodiment is as follows:
[0087] S01: The flake graphene is first mixed with a sufficient amount of a 2% by mass hydrochloric acid solution, then washed with water and dried, the dried flake graphene is heat treated at 230°C for 10 min, and then the reaction temperature is cooled to 60°C at a rate of 5°C / min, kept warm, and set aside;
[0088] S02: Preparation of stress solution:
[0089] S021: 4 parts of carboxymethyl cellulose are added to 8 parts of sodium lignin sulfonate solution, followed by 2 parts of stearic acid and 0.35 parts of silane coupling agent KH550 to obtain a conditioning solution;
[0090] S022: adding nano-silicon dioxide into the phosphate buffer solution at a weight ratio of 2:7 and mixing thoroughly to obtain a nano-silicon dioxide dispersion;
[0091] S023: The nano-silicon dioxide dispersion and the toning liquid are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h to obtain a stress liquid;
[0092] S03: The flake graphene kept warm in S01 and the stressing liquid are stirred in a weight ratio of 3:7. After the stirring is completed, the mixture is filtered and dried to obtain a stressing modifier based on flake graphene.
[0093] The pH value of the phosphate buffer solution in this example is 5.5; the mass fraction of the sodium lignin sulfonate solution is 6%.
[0094] In the present embodiment, the stirring process is first carried out at a stirring speed of 850 r / min for 15 min, and then the speed is reduced to 350 r / min and stirring is continued for 40 min.
[0095] The preparation method of the tonic and synergistic agent of this embodiment is:
[0096] S11: treating the silicon carbide whiskers with proton irradiation at a power of 450 W for 15 minutes, and obtaining irradiated whiskers after the irradiation is completed;
[0097] S12: immersing the irradiated whiskers into a sufficient amount of lanthanum solution until fully immersed, filtering and drying after the immersion is completed, to obtain a lanthanum-modified whisker agent;
[0098] S13: The lanthanum-modified whisker agent and the hydroxyapatite-doped restorative modifying liquid are mixed and ball-milled in a weight ratio of 5:2. After the ball milling is completed, the mixture is washed with water and dried to obtain a restorative modifying agent. The mixing ball milling speed is 1500 r / min and the ball milling is performed for 1 hour.
[0099] The lanthanum solution of this embodiment is a lanthanum nitrate solution with a mass fraction of 5%; the ultrasonic power for full immersion is 380W, and the immersion time is 25min.
[0100] The preparation method of the hydroxyapatite-doped remedial modified liquid of this embodiment is as follows:
[0101] The hydroxyapatite, chitosan solution and nano-silica sol are first mixed thoroughly in a weight ratio of 5:9:1 to obtain a compounding solution;
[0102] Yttrium oxide and sodium dodecylbenzene sulfonate solution are mixed in a weight ratio of 2:5 to obtain yttrium oxide agent; then, 10% of the yttrium oxide agent and 5% of the sodium alginate are added to the reconstituted liquid, and the mixture is further fully mixed to obtain a hydroxyapatite-doped remedial modified liquid.
[0103] The mass fraction of the chitosan solution in this embodiment is 5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 8%.
[0104] The method for preparing a water-resistant and rust-proof quick-drying epoxy alkyd varnish of the present embodiment comprises the following steps: the raw materials are mixed uniformly according to a proportion to obtain the quick-drying epoxy alkyd varnish of the present invention.
[0105] Embodiment 3:
[0106] The water-resistant and rust-proof quick-drying epoxy alkyd varnish of the present embodiment comprises the following raw materials in parts by weight:
[0107] 40 parts of epoxy alkyd resin, 10 parts of flaky graphene-based stress modifier, 6 parts of soybean oil, 6 parts of compensating agent, 5 parts of silane coupling agent, 5 parts of curing agent, 0.25 parts of drying agent, and 32.5 parts of solvent.
[0108] The preparation method of the epoxy alkyd resin of the present embodiment is as follows: a polyol of neopentyl glycol and a polyacid of adipic acid are mixed in a weight ratio of 1:2, xylene accounting for 15% of the total amount of neopentyl glycol is added, the mixture is heated to 120° C. for reaction for 1.5 hours, and then the mixture is heated to 160° C. for reaction until complete to obtain an alkyd resin; a bisphenol A type epoxy resin, an alkyd resin and triethanolamine are mixed in a weight ratio of 10:40:1.5, the mixture is heated to 105° C. for reaction for 3 hours, and the material is filtered to obtain an epoxy modified alkyd resin;
[0109] The drying agent is butyl tin oxide; the solvent is ethyl acetate solvent; the curing agent is ethylenediamine; and the silane coupling agent is silane coupling agent KH560.
[0110] The preparation method of the graphene-based stress modifier of this embodiment is as follows:
[0111] S01: The flake graphene is first mixed with a sufficient amount of a 2% by mass hydrochloric acid solution, then washed with water and dried, the dried flake graphene is heat treated at 220°C for 7.5 min, and then the reaction temperature is cooled to 60°C at a rate of 3.5°C / min, kept warm, and set aside;
[0112] S02: Preparation of stress solution:
[0113] S021: 3 parts of carboxymethyl cellulose are added to 6.5 parts of sodium lignin sulfonate solution, followed by 1.5 parts of stearic acid and 0.30 parts of silane coupling agent KH550 to obtain a conditioning solution;
[0114] S022: adding nano-silicon dioxide into the phosphate buffer solution at a weight ratio of 1:3 and mixing thoroughly to obtain a nano-silicon dioxide dispersion;
[0115] S023: The nano-silicon dioxide dispersion and the toning liquid are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h to obtain a stress liquid;
[0116] S03: The flake graphene kept warm in S01 and the stressing liquid are stirred in a weight ratio of 3:7. After the stirring is completed, the mixture is filtered and dried to obtain a stressing modifier based on flake graphene.
[0117] The pH value of the phosphate buffer solution in this example is 5.25; the mass fraction of the sodium lignin sulfonate solution is 5%.
[0118] In the present embodiment, the stirring process was first carried out at a stirring speed of 800 r / min for 12.5 min, and then the speed was reduced to 325 r / min and the stirring was continued for 37.5 min.
[0119] The preparation method of the tonic and synergistic agent of this embodiment is:
[0120] S11: treating the silicon carbide whiskers with proton irradiation at a power of 420 W for 12.5 min, and obtaining irradiated whiskers after the irradiation is completed;
[0121] S12: immersing the irradiated whiskers into a sufficient amount of lanthanum solution until fully immersed, filtering and drying after the immersion is completed, to obtain a lanthanum-modified whisker agent;
[0122] S13: The lanthanum-modified whisker agent and the hydroxyapatite-doped restorative modifying liquid are mixed and ball-milled in a weight ratio of 5:2. After the ball-milling is completed, the mixture is washed with water and dried to obtain a restorative modifying agent. The mixing ball-milling speed is 1250 r / min and the ball-milling is performed for 1 hour.
[0123] The lanthanum solution of this embodiment is a lanthanum nitrate solution with a mass fraction of 3.5%; the ultrasonic power for full immersion is 360W, and the immersion time is 20min.
[0124] The preparation method of the hydroxyapatite-doped remedial modified liquid of this embodiment is as follows:
[0125] The hydroxyapatite, chitosan solution and nano-silica sol are first mixed thoroughly in a weight ratio of 4:6:1 to obtain a compounding solution;
[0126] Yttrium oxide and sodium dodecylbenzene sulfonate solution are mixed in a weight ratio of 2:5 to obtain yttrium oxide agent; then, 7.5% of the yttrium oxide agent and 2-5% of the sodium alginate are added to the reconstituted liquid, and the mixture is fully mixed to obtain a hydroxyapatite-doped remedial modified liquid.
[0127] The mass fraction of the chitosan solution in this embodiment is 3.5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 6.5%.
[0128] The method for preparing a water-resistant and rust-proof quick-drying epoxy alkyd varnish of the present embodiment comprises the following steps: the raw materials are mixed uniformly according to a proportion to obtain the quick-drying epoxy alkyd varnish of the present invention.
[0129] Comparative Example 1.
[0130] The difference from Example 3 is that no flaky graphene-based stress modifier is added.
[0131] Comparative Example 2.
[0132] Different from Example 3, step S01 is not used in the preparation of the graphene flake-based stress modifier.
[0133] Comparative Example 3.
[0134] Different from Example 3, no stress liquid treatment was used in the preparation of the stress modifier based on flake graphene.
[0135] Comparative Example 4.
[0136] The difference from Example 3 is that no nano-silicon dioxide dispersion is added in the preparation of the stress solution.
[0137] Comparative Example 5.
[0138] The difference from Example 3 is that no toning liquid is added in the preparation of the stress liquid.
[0139] Comparative Example 6.
[0140] The difference from Example 3 is that no tonic agent is added.
[0141] Comparative Example 7.
[0142] The difference from Example 3 is that the compensating and regulating agent is not fully treated by immersing in the lanthanum solution.
[0143] Comparative Example 8.
[0144] The difference from Example 3 is that the restorative and synergistic agent is not treated with a restorative and modifying liquid doped with hydroxyapatite.
[0145] The product performance of Examples 1-3 and Comparative Examples 1-8 was tested, and the determination method was as follows:
[0146]
[0147] It is concluded from Examples 1-3 and Comparative Examples 1-8 that
[0148] The product of Example 3 of the present invention has excellent impact resistance and surface drying performance, and the product has significant salt spray resistance and water resistance stability effects;
[0149] From comparative examples 1-8, it can be seen that without adding the emphasizing modifier based on flake graphene and without adding the synergistic agent, the performance of the product has a significant trend of deterioration. The performance effect of the product is most significant when the two are coordinated and work together.
[0150] The performance of the product tends to deteriorate when the step S01 is not used in the preparation of the emphasized modifier based on flake graphene, the emphasized liquid is not used in the preparation of the emphasized modifier based on flake graphene, the nano-silicon dioxide dispersion is not added in the preparation of the emphasized liquid, and the toning liquid is not added in the preparation of the emphasized liquid. The performance effect of the product is the most significant when the emphasized modifier based on flake graphene is prepared by combining the emphasized liquid obtained by combining the nano-silicon dioxide dispersion and the toning liquid of the present invention with the step S01 of the present invention. The emphasized modifier based on flake graphene obtained by using the specific raw material formula and process of the present invention has significant product performance effect. The use of other methods instead is not as obvious as the effect of the present invention.
[0151] When the restoring and synergistic agent was not fully treated by immersing in lanthanum solution, and when the restoring and synergistic agent was not treated with restoring and modifying liquid doped with hydroxyapatite, the product performance tended to deteriorate, and when the restoring and synergistic agent was not treated with restoring and modifying liquid doped with hydroxyapatite, the product performance deteriorated more significantly.
[0152] The performance of the product has been greatly changed by the modified liquid based on doping hydroxyapatite. Further research on this is as follows:
[0153] Experimental Example 1
[0154] The only difference from the example is that no yttrium oxide agent is added in the preparation of the hydroxyapatite-doped restorative modification liquid.
[0155] Experimental Example 2
[0156] The only difference from the example is that no sodium alginate is added in the preparation of the tonic modified liquid doped with hydroxyapatite.
[0157] Experimental Example 3
[0158] The only difference from Example 3 is that no re-adjusting liquid is added in the preparation of the hydroxyapatite-doped tonic modifying liquid.
[0159] Experimental Example 4
[0160] The only difference from Example 3 is that no hydroxyapatite or nano-silica sol is added to the reconstitution solution.
[0161]
[0162] It can be seen from Experimental Examples 1-4 that when no re-adjusting liquid is added in the preparation of the tonic modifying liquid doped with hydroxyapatite, the performance of the product deteriorates most significantly, followed by when no yttrium oxide is added. At the same time, when no hydroxyapatite and nano-silica sol are added to the re-adjusting liquid, the performance of the product also shows a relatively obvious deterioration trend. The preparation of the re-adjusting liquid is proprietary, and the effect of using other methods instead is not as good as the technical solution of the present invention. In addition, when no sodium alginate is added in the preparation of the tonic modifying liquid doped with hydroxyapatite, the performance of the product also shows a deterioration trend. The re-adjusting liquid obtained by the method of the present invention is combined with yttrium oxide and sodium alginate, and the performance effect of the product is the most significant, and the effect of using other methods instead is not as obvious as the effect of the present invention.
[0163] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0164] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A water-resistant and rust-proof quick-drying epoxy alkyd varnish, characterized in that: It includes the following raw materials in parts by weight: 35-45 parts of epoxy alkyd resin, 8-12 parts of flaky graphene-based modifier, 4-8 parts of soybean oil, 5-7 parts of synergist, 4-6 parts of silane coupling agent, 4-6 parts of curing agent, 0.2-0.3 parts of drying agent, and 30-35 parts of solvent; The preparation method of the graphene-based stress modifier is as follows: S01: The flake graphene is first mixed with a sufficient amount of a 2% hydrochloric acid solution, then washed with water and dried, the dried flake graphene is heat treated at 210-230°C for 5-10 minutes, and then the reaction temperature is cooled to 60°C at a rate of 2-5°C / min, kept warm, and set aside; S02: Preparation of stress solution: S021: Add 2-4 parts of carboxymethyl cellulose to 5-8 parts of sodium lignin sulfonate solution, and then add 1-2 parts of stearic acid and 0.25-0.35 parts of silane coupling agent KH550 to obtain a conditioning solution; S022: Add nano-silicon dioxide into the phosphate buffer solution in a weight ratio of 2:(5-7) and mix thoroughly to obtain a nano-silicon dioxide dispersion; S023: The nano-silicon dioxide dispersion and the toning liquid are mixed and ball-milled in a weight ratio of 5:3 at a ball-milling speed of 1500 r / min for 1 h to obtain a stress liquid; S03: stirring the flake graphene and the stressing liquid kept warm in S01 at a weight ratio of 3:7, filtering and drying after the stirring is completed, to obtain a stressing modifier based on flake graphene; The preparation method of the tonic and synergistic agent is as follows: S11: treating the silicon carbide whiskers with proton irradiation at a power of 400 to 450 W for 10 to 15 minutes, and obtaining irradiated whiskers after the irradiation is completed; S12: immersing the irradiated whiskers into a sufficient amount of lanthanum solution until fully immersed, filtering and drying after the immersion is completed, to obtain a lanthanum-modified whisker agent; S13: mixing the lanthanum-modified whisker agent and the hydroxyapatite-doped synergistic modifying liquid in a weight ratio of 5:2, and then ball-milling the mixture. After the ball-milling is completed, the mixture is washed with water and dried to obtain a synergistic agent. The mixing ball-milling speed is 1000-1500 r / min, and the ball-milling is performed for 1 hour. The preparation method of the epoxy alkyd resin is as follows: a polyol of neopentyl glycol and a polyacid of adipic acid are mixed in a weight ratio of 1:2, xylene accounting for 15% of the total amount of neopentyl glycol is added, the mixture is heated to 120° C. for reaction for 1 to 2 hours, and then the mixture is heated to 160° C. for reaction until the mixture is completely reacted to obtain an alkyd resin; a bisphenol A type epoxy resin, an alkyd resin and triethanolamine are mixed in a weight ratio of 10:40:1.5, the mixture is heated to 105° C. for reaction for 2 to 4 hours, and the material is filtered to obtain an epoxy modified alkyd resin; The drying agent is butyl tin oxide; the solvent is ethyl acetate solvent; the curing agent is ethylenediamine; the silane coupling agent is silane coupling agent KH560; The preparation method of the hydroxyapatite-doped tonic modified liquid is as follows: The hydroxyapatite, chitosan solution and nano-silica sol are first mixed thoroughly in a weight ratio of (3-5): (7-9): 1 to obtain a compounding solution; Yttrium oxide and sodium dodecylbenzene sulfonate solution are mixed in a weight ratio of 2:5 to obtain yttrium oxide agent; then, 5-10% of the total amount of the re-adjusting liquid and 2-5% of the total amount of sodium alginate are added to the re-adjusting liquid, and the mixture is further fully mixed to obtain a hydroxyapatite-doped remedial modified liquid.
2. A water-resistant and rust-proof quick-drying epoxy alkyd varnish according to claim 1, characterized in that: The pH value of the phosphate buffer solution is 5.0-5.5; the mass fraction of the sodium lignin sulfonate solution is 4-6%.
3. A water-resistant and rust-proof quick-drying epoxy alkyd varnish according to claim 1, characterized in that: The stirring treatment is first carried out at a stirring speed of 750 to 850 r / min for 10 to 15 minutes, and then the speed is reduced to 300 to 350 r / min, and the stirring is continued for 35 to 40 minutes.
4. A water-resistant and rust-proof quick-drying epoxy alkyd varnish according to claim 1, characterized in that: The lanthanum solution is a lanthanum nitrate solution with a mass fraction of 2 to 5%. The ultrasonic power for full immersion is 350 to 380 W, and the immersion time is 15 to 25 minutes.
5. A water-resistant and rust-proof quick-drying epoxy alkyd varnish according to claim 1, characterized in that: The mass fraction of the chitosan solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 5-8%.
6. A process for preparing the water-resistant and rust-proof quick-drying epoxy alkyd varnish according to any one of claims 1 to 5, characterized in that: The following steps are involved: The raw materials are mixed evenly according to the proportions to obtain quick-drying epoxy alkyd varnish.
Citation Information
Patent Citations
Preparation method of graphene antibacterial water-based paint
CN116656186A
Method for preparing low melting point metal particles, conductive paste and method for preparing the same
US20230162882A1